PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV A SD NEGERI SRONDOL KULON 02 SEMARANG - Nurul Maesaroh; Nursiwi Nugraheni; Teguh Budi Prakoso (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Education in the 21st century must be able to keep pace with developments in order to create an educated and qualified generation. 21st century skills, such as critical thinking, creativity, communication, and collaboration, need to be instilled through effective learning. This research aims to improve Pancasila education learning outcomes through the Problem Based Learning Model for class IVA students at SD Negeri Srondol Kulon 02 Semarang. The research method used is Classroom Action Research with 3 cycles. The subjects of this research were 28 class IVA students at SD Negeri Srondol Kulon 02. Data collection was carried out through test methods, observation, field notes and documentation. The PBL model is applied by paying attention to aspects such as apperception, relating material, using fun learning strategies, and supporting media. The research results showed that the level of students' understanding increased from 36% with an average of 69 to 68% with an average of 75 in cycle I, while in cycle II it increased to 79% with an average of 84.00. and from cycle III there was a significant increase or 96% with the number of students as many as 27 students. Based on the research results, it was concluded that the use of the PBL model had a positive impact on students' enthusiasm and involvement in learning. Therefore, the PBL model can effectively improve Pancasila education learning outcomes for class IV A students at SD Negeri Srondol Kulon 02 Semarang.